Women and Shari‘Ah Law: Lessons from Aceh - Asna Husin (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2015)
This study surveys the role of women in the development of shari`ah from the introduction of Islam to Aceh in the 12th centurydown to the modern erawith the formal adoption of Islamic law by an Indonesian parliamentary Bill on Aceh’s Special Status in 1999. After briefly exploring this history, we examine contemporary debates on the current implementation of Islamic law by means of five women of differing backgrounds in this Indonesian province. We review historical documents and existing literature as well as qanuns of Aceh (local regulations) which stipulate shari`ah requirements. We also interview the five women, including one whose husband and another who herself were subjected to shari`ah punishment. The results are complex reflecting the intricacy of contemporary understandings of the shari`ah and the issues surrounding rights of women in Islamic law. One voice represents her agreement to the shari`ah punishment of her husband on account of its positive outcome for her family. The other four are critical of the current implementation of the shari`ah in Aceh, yet are not opposed to it; these ladies argue for women friendly shari`ah.